Migration Regimes and the Translation of Human Rights: On the Struggles for Recognition of Romani Migrants in Germany - Jure Leko (Social Inclusion, 2017)
The current claims for asylum and refugee protection of Roma from the so-called “Western Balkan states” are rejected by the German state. Based on this practice, Romani migrants are not recognized as genuine refugees but classified as irregular migrants and thus labeled as “bogus” asylum seekers. This article discusses the discursive process through which the legal status of Romani migrants is irregularized within the German migration regime. Furthermore, through an empirical study, the article shows how Romani organizations and migrants are struggling for a collective right to remain in Germany. In their political-legal struggles for recognition, Roma reinterpret not only their legal status as irregular migrants, but also their legal-cultural practices: by appropriating the semantics of human rights through the lenses of their cultural backgrounds. This, in turn, shifts the analytical focus to the productivity of human rights discourses. They are assumed to be an effective tool to enforce legal claims against the German migration regime. In this context, the article examines legal-cultural practices, which become visible in the struggle, by exploring six justification narratives—through these, the Roma’s political-legal belonging to the German nation-state shall be legitimized.